INTENSI KEWIRAUSAHAAN DAN KECERDASAN EMOSIONAL PENGARUHNYA TERHADAP KEYAKINAN DIRI MAHASISWA PERGURUAN TINGGI DI SULAWESI SELATAN: STUDI KASUS PADA MAHASISWA MANAJEMEN UNIVERSITAS NEGERI MAKASSAR - Sahabuddin, Romansyah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the influence of entrepreneurial intention and emotional intelligence on the self-efficacy of university students in South Sulawesi, particularly students of the Management Study Program at Makassar State University. This research is based on the low number of entrepreneurs in Indonesia compared to neighboring countries, as well as the need to empower the younger generation through psychological approaches and entrepreneurship education. This study is quantitative with a survey approach using questionnaires distributed to 255 respondents. The variables studied are entrepreneurial intention, emotional intelligence, and self-efficacy. The analytical method used is multiple linear regression to determine the partial and simultaneous effects between variables. This study adds novelty by combining psychological aspects (emotional intelligence) and entrepreneurial intention in predicting student self-efficacy, an approach that is still rarely used. The expected result is the identification of a significant relationship between entrepreneurial intention and emotional intelligence on student self-efficacy, both partially and simultaneously.